Decrease of PPARδ in Type-1-Like Diabetic Rat for Higher Mortality after Spinal Cord Injury. (10th April 2014) - Tsai, Cheng-Chia; Lee, Kung-Shing; Chen, Sheng-Hsien; Chen, Li-Jen; Liu, Keng-Fan; Cheng, Juei-Tang
Abstract : Changes in the peroxisome proliferator-activated receptors- δ (PPAR δ ) expression in rats after spinal cord injury (SCI) have been previously reported. Diabetic animals show a higher mortality after SCI. However, the relationship between the progress of diabetes and PPAR δ in SCI remains unknown. In the present study, we used compressive SCI in streptozotocin-(STZ-) induced diabetic rats. GW0742, a PPAR δ agonist, was used to evaluate its merit in STZ rats after SCI. Changes in PPAR δ expression were detected by Western blot. Survival rates were also estimated. A lower expression of PPAR δ in spinal cords of STZ-diabetic rats was observed. In addition, the survival times in two-week induction diabetes were longer than those in eight-week induction group, which is consistent with the expression of PPAR δ in the spinal cord. Moreover, GW0742 significantly increased the survival time of STZ rats. Furthermore, their motor function and pain response were attenuated by GSK0660, a selective PPAR δ antagonist, but were enhanced by GW0742. In conclusion, the data suggest that higher mortality rate in STZ-diabetic rats with SCI is associated with the decrease of PPAR δ expression. Thus, change of PPAR δ expression with the progress of diabetes seems responsible for the higher mortality rate after SCI.